Penatalaksanaan Kegawatdaruratan Kecelakaan Karena Ubur-ubur dan Bulu Babi pada Masyarakat pulau - Gobel, Iswanto; Welembuntu, Meistvin; Tuwohingide, Yanli Everson (Lontara Journal of Health Science and Technology, 2024)
The island population uses the sea as a source of livelihood and as a place for recreation so many accidents in the sea such as bites and punches caused by marine animals. The design was descriptive with a cross-sectional approach, taking data at one time with a total sample of 246 people divided into four region clusters. The results found that most of the population (50%) gave kicked to destroy action on the treatment of pork sting while for the action of spruce-fertilizer, most of the community (35%) gave action of orange sting. The sting action given on the kicking and sting of marine animals based on local wisdom of kicked-to-destroy and the provision of oranges sting, it is preferable to carry out advanced research related to the impact and scientific investigation of the effects of such action besides it is also recommended that the material of the handling of the seabed be included in the school curriculum and socialized to the community.